Pilgrims' Reception in Living Qur'an Study: Recitation of Tafsir Al-Ibriz at LPPQ Al-Karim - Fikri, Muhammad Nahjul; Sihono, Sihono; Mubarok, Hadziq (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study discusses the congregation's reception of the Tafsir Al-Ibriz in religious studies at LPPQ Al-Karim as a form of implementation of the Living Qur'an study. The focus of the study is how the congregation accepts and internalizes the teachings of the interpretation in the context of their social life. A qualitative approach with a case study method is used to explore the interaction between religious texts and the social context of the congregation. Primary data were collected through in-depth interviews and participant observations, while secondary data were obtained from related literature. The results of the study indicate that the Al-Ibriz interpretation, which uses Javanese, plays a significant role in bridging the understanding of the text of the Qur'an with the reality of local community life. The congregation feels spiritual transformation, increased religious insight, and changes in more positive social behavior. This study highlights the importance of a local approach in religious studies to strengthen relevant and applicable religious understanding. This study provides theoretical contributions to the study of the Living Qur'an, as well as practical contributions for managers of religious study institutions in designing programs based on the needs of the congregation.